2010
DOI: 10.1161/circulationaha.110.953208
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Macrophage Migration Inhibitory Factor–AMP-Activated Protein Kinase Activation and Ischemic Recovery in the Senescent Heart

Abstract: Background-Elderly patients are more sensitive than younger patients to myocardial ischemia, which results in higher mortality. We investigated how aging affects the cardioprotective AMP-activated protein kinase (AMPK) signaling pathway. Methods and Results-Ischemic AMPK activation was impaired in aged compared with young murine hearts. The expression and secretion of the AMPK upstream regulator, macrophage migration inhibitory factor (MIF), were lower in aged compared with young adult hearts. Additionally, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
166
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 157 publications
(172 citation statements)
references
References 42 publications
4
166
1
1
Order By: Relevance
“…Mouse hearts were perfused in the Langendorff mode with oxygenated Krebs-Henseleit buffer containing 7 mmol/L glucose, 0.4 mmol/L oleate, 1% BSA, and a low fasting concentration of insulin (10 μU/mL), as previously described (22,55). For ischemia/reperfusion studies, hearts were stabilized at a flow rate of 4 mL/min for 30 min before 15-20 min of no-flow global ischemia, with or without 30 min of reperfusion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mouse hearts were perfused in the Langendorff mode with oxygenated Krebs-Henseleit buffer containing 7 mmol/L glucose, 0.4 mmol/L oleate, 1% BSA, and a low fasting concentration of insulin (10 μU/mL), as previously described (22,55). For ischemia/reperfusion studies, hearts were stabilized at a flow rate of 4 mL/min for 30 min before 15-20 min of no-flow global ischemia, with or without 30 min of reperfusion.…”
Section: Methodsmentioning
confidence: 99%
“…Myocardial infarction was assessed in hearts excised after 20 min ischemia and 3 h of reperfusion. The heart was stained to delineate the extent of necrosis as a percent of the nonperfused area at risk distal to the coronary occlusion (22,55).…”
Section: Methodsmentioning
confidence: 99%
“…Highlighting the role of MIF in inflammation, diverse studies have shown that inhibition of MIF can mitigate deleterious inflammation in conditions such as ARDS, asthma, sepsis, and autoimmunity (8,38,86,120,146). In addition to its immunological function, MIF promotes cellular survival, antioxidant signaling, angiogenesis, and wound repair while mitigating cellular senescence (2,4,21,29,42,47,57,80,82,87,99,100,123,160). This review will highlight the role of MIF in the pathogenesis of respiratory diseases that disproportionately afflict the elderly.…”
mentioning
confidence: 99%
“…MIF regulates key functions in myocardial ischemia/reperfusion (I/R) injury with an overall cardioprotective activity profile. [11][12][13][14] Mechanistically, this property involves protection against c-Jun N-terminal kinase (JNK)-mediated apoptosis and against oxidative cell stress which prominently occurs during the early phase of reperfusion in myocardial infarction. Protection conferred by MIF against redox stress has been attributed to its intrinsic thiol-protein oxidoreductase (TPOR) activity.…”
mentioning
confidence: 99%